The whole genome sequence data analyses of a mycobacterium tuberculosis strain sbh321 isolated in Sabah, Malaysia, belongs to ural family of lineage 4 - Jaeyres Jani; Zainal Arifin Mustapha; Chin Kai Ling; Amabel Seow Ming Hui; Roddy Teo; Kamruddin Ahmed (Elsevier Ltd, 2020)
In 2019, 10 million new cases of tuberculosis have been re- ported worldwide. Our data reports genetic analyses of a My- cobacterium tuberculosis strain SBH321 isolated from a 31- year-old female with pulmonary tuberculosis. The genomic DNA of the strain was extracted from pure culture and sub- jected to sequencing using Illumina platform. M. tuberculosis strain SBH321 consists of 4,374,895 bp with G + C content of 65.59%. The comparative analysis by SNP-based phylogenetic analysis using maximum-likelihood method showed that our strain belonging to sublineage of the Ural family of Europe–America–Africa lineage (Lineage 4) and clustered with M. tuberculosis strain OFXR-4 from Taiwan. The whole genome sequence is deposited at DDBJ/ENA/GenBank under the ac- cession WCJH0 0 0 0 0 0 0 0 (SRR10230353).